Technology Adoption and Social Issues 2018
DOI: 10.4018/978-1-5225-5201-7.ch001
|View full text |Cite
|
Sign up to set email alerts
|

Technology Acceptance Theories

Abstract: Studying the acceptance and usage of technologies has become one of the most significant fields in software engineering domain. In order to explain the individuals' usage behavior towards technologies, many theories and models have been proposed over the years. This research paper focuses on reviewing a group of ten technology acceptance theories and models by studying their structure, evolution stages, and their strengths and weaknesses points. These theories were analyzed and classified into two main types d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 37 publications
0
36
0
2
Order By: Relevance
“…The major goal of the TAM framework is to understand the behavioral intention of users (acceptance) toward and their actual use of a technology [ 36 , 37 ]. Davis suggested that future technology acceptance studies should focus on other principles that influence usefulness, ease of use, and user acceptance [ 37 ]. Thus, price-value, trust, and perceived risk factors were used to extend the TAM framework in this study.…”
Section: Introductionmentioning
confidence: 99%
“…The major goal of the TAM framework is to understand the behavioral intention of users (acceptance) toward and their actual use of a technology [ 36 , 37 ]. Davis suggested that future technology acceptance studies should focus on other principles that influence usefulness, ease of use, and user acceptance [ 37 ]. Thus, price-value, trust, and perceived risk factors were used to extend the TAM framework in this study.…”
Section: Introductionmentioning
confidence: 99%
“…The level of acceptance of information technology by the user can be predicted from the attitudes and perceptions of the users of these technologies, such as the desire to add support tools or seek support such as support, motivation to continue to use, as well as the desire to affect other users. Theories and models regarding acceptance of technology has also been developed since the 1980s by a variety of variables (Momani & Jamous, 2017), In general, the variables in a variety of models that have been used are explained that intrinsic motivation, experience, and social conditions play a major role in the acceptance of the technology, so it can be generalized that the behavior (behavior) the user plays an important role in the decision making in the use of technology. Based on the review of some of the above studies, behavioral intention in this study can be defined as factors that affect the user to continue using the service GWJ application.…”
Section: Behavior Intentionmentioning
confidence: 99%
“…This study is based on the Technology Acceptance Model (TAM) propounded by Davis (1989) and advocated by Lai (2017). The TAM is an information systems theory that models how users come to accept and use a particular technology (Mugo et al, 2017;Momani & Jamous, 2017). Park (2009) argues that TAM is considered an influential extension of theory of reasoned action (TRA), according to Ajzen and Fishbein (1980).…”
Section: Technology Acceptance Model and Electronic Payment System Admentioning
confidence: 99%
“…According to TAM, one's actual use of a technology system is influenced directly or indirectly by the user's behavioural intentions, attitude, perceived usefulness of the system, and perceived ease of the system (Folkinshteyn & Lennon, 2016;Park 2009). TAM also proposes that external factors affect intention and actual use through mediated effects on perceived usefulness and perceived ease of use (Momani & Jamous, 2017;Sargolzaei, 2017). He further argues that TAM appears to be able to account for more than 50 percent of user acceptance.…”
Section: Technology Acceptance Model and Electronic Payment System Admentioning
confidence: 99%